A Pedestrian Route to Soeiro - Graça, C.; Macieira, C.; Almeida, F.; Manso, L. (Open Schools Journal for Open Science, 2020)
The project aimed to requalify the space between the S. António river and the Arruda road, creating access to the Soeiro Pereira Gomes school, protecting it from motor vehicles. A pedestrian route was outlined and creative solutions of urban furniture (bench, garbage can, lighting and drinking fountain) to be placed along the route were developed. The municipal entities were involved, however only the President of the Union of Parishes was available for the implementation of the project.